বাংলাদেশের উন্নয়ন ও দারিদ্র্য দূরীকরণের রাজনৈতিক অর্থনীতি - হোসেন, আমজাদ (ঢাকা : পড়ুয়া, 1995)
On economic development and poverty alleviation in Bangladesh.
In Bengali.
Includes bibliographical references (p. 163-168).
Keywords: Poverty -- Bangladesh; Bangladesh -- Economic policy